Diffusion-weighted Imaging Patterns of Brain Damage Associated with Cerebral Venous Thrombosis - Ducreux, Denis; Oppenheim, Catherine; Vandamme, Xavier; Dormont, Didier; Samson, Yves; Rancurel, Gérald; Cosnard, Guy; Marsault, Claude (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Apart from cases studies, little is known regarding diffusion-weighted imaging of brain lesions associated with human cerebral venous thrombosis (CVT). Our aim was to describe the initial diffusion-weighted imaging patterns observed in brain areas with MR signal changes associated with CVT and to compare them with those of follow-up imaging.METHODS: The cases of nine patients with brain lesions associated with CVT who underwent CT and diffusion-weighted imaging 3 hours to 4 days after sudden neurologic onset were retrospectively reviewed. The apparent diffusion coefficient (ADC) in abnormal brain was compared with that of contralateral normal regions using z score analysis. MR images obtained during 3 to 6 months of follow-up were available for seven patients.RESULTS: All patients had nonhemorrhagic T2-hyperintense brain regions. These were associated with partially hemorrhagic areas on the CT scans of four patients. In nonhemorrhagic edematous areas, ADC was heterogeneous (coexistence of increased, normal, or decreased ADC) in five patients and homogeneous in four. In the latter four patients, ADC values were within normal range in three, whereas a large homogeneous hyperintensity with decreased ADC values (0.3–0.4 10−3mm2/s, <−3 z scores) was observed in one. When available, follow-up images always showed hemorrhagic sequelae in initially hemorrhagic areas. Nonhemorrhagic edematous areas with initially increased ADC values returned to normal. Initially normal or decreased ADC values were predictive of reversibility, although imaging sequelae were rarely observed.CONCLUSION: The diffusion-weighted imaging/ADC pattern of venous stroke is more heterogeneous than previously thought. Large brain regions of reduced ADC values that are not predictive of ultimate infarction in cases of CVT can be observed.